2013
DOI: 10.1111/jace.12335
|View full text |Cite
|
Sign up to set email alerts
|

Glass Formation and Characterization Studies in the TeO2WO3Na2O System

Abstract: Glass formation behavior of the TeO2–WO3–Na2O system was studied by using conventional melt‐quenching technique. A wide glass formation range was determined for the first time in the literature and thermal, physical, and structural characterization of sodium‐tungsten‐tellurite glasses were realized using differential scanning calorimetry (DSC) and Fourier transform infrared (FTIR) spectroscopy techniques. Glass transition (Tg) and crystallization (Tc/Tp) temperatures, glass stability (∆T), density (ρ), molar v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(23 citation statements)
references
References 22 publications
(84 reference statements)
1
21
1
Order By: Relevance
“…The Ag + ions further transform into the Ag nanoparticles after the heat treatment. Previous investigation demonstrated that the W–O − nonbridging oxygen was formed in the TeO 2 –WO 3 –Na 2 O . The formation of Ag nanoparticles in the tellurite glass may be related to the presence of the W–O − .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The Ag + ions further transform into the Ag nanoparticles after the heat treatment. Previous investigation demonstrated that the W–O − nonbridging oxygen was formed in the TeO 2 –WO 3 –Na 2 O . The formation of Ag nanoparticles in the tellurite glass may be related to the presence of the W–O − .…”
Section: Resultsmentioning
confidence: 94%
“…Previous investigation demonstrated that the W-O À nonbridging oxygen was formed in the TeO 2 -WO 3 -Na 2 O. 46 The formation of Ag nanoparticles in the tellurite glass may be related to the presence of the W-O À . The Ag + ions were reduced to Ag 0 by the W-O À during the heat treatment, and many Ag 0 were aggregated and grown into Ag nanoparticles.…”
Section: Effect Of Ag Nanoparticles On Photoluminescence Of Eu 3+ -mentioning
confidence: 94%
See 1 more Smart Citation
“…The formation of Au nanoparticles in the tellurite glass may be related to the presence of the W–O − . Çelikbilek et al reported that the non‐bridging oxygen species W–O − was formed in the TeO 2 –WO 3 –Na 2 O glasses which were characterized by the FT‐IR spectra . Gold ions were introduced into the glass host by AuCl 3 during the heat treatment.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Maaß et al [23] proposed that Raman bands at 250 to 970 cm À 1 observed in Li 2 B 4 O 7 -WO 3 glasses are due to WO 4 2 À tetrahedral units and the presence of W 2 O 7 2 À structure. Celikbilek et al [24] suggested the presence of both WO 4 and WO 6 units in Na 2 O-WO 3 -TeO 2 glasses from Fourier transform infrared spectra. Gugov et al [25] also proposed the presence of WO 4 and WO 6 units in TeO 2 -WO 3 glasses from Raman scattering spectra.…”
Section: Raman Scattering Spectra Of Glassesmentioning
confidence: 99%